Análises, aplicações e validações–numérico/experimentais do modelo SWAN em áreas restritas e ao largo - Vieira, Adriana Silveira [UNESP] (2013)
This research deals with the monitoring and the forecasting of wind wave generation and propagation at Praia da Vitória – Azores - Portugal and at the reservoir of Ilha Solteira Dam – São Paulo – Brazil. The SWAN numerical model (Simulating Waves Nearshore) is employed. Such a model is able to simulate the generation, propagation and dissipation of sea waves, based on the equation for wave action conservation. In the sea-wave propagation across both open and confined coastal regions, the model simulates the physical processes of refraction, diffraction and shoaling due to bottom depth variations. It also is capable of simulate the presence of currents, as well as wave growth due to wind, bottom induced wave breaking and whitecapping, energy dissipation due to bottom friction, wave blocking and reflection by currents and wave transmission across obstacles. Among the several results produced by SWAN model, it is worth mentioning significant wave height, mean and peak periods, mean and peak directions, directional spreading, bandwidth parameter and sea level anywhere in the computational domain. Two applications of SWAN model are developed to simulate sea-wave generation and propagation at two distinct locations: one corresponds to an open coast location – the maritime region adjacent to Praia da Vitória port, on Terceira Island, Azores archipelago, Portugal; and the other corresponding to a confined region, the reservoir of Ilha Solteira Dam, São Paulo, Brazil. For Praia da Vitória port, results from offshore sea wave forecasts obtained through the large scale model WAVEWATCH III and wind data from MM5 model were used as forcing data for SWAN model. The numerical results were compared to sea-wave data obtained from a wave buoy deployed 4 km away from the coast at water depth of 90 m (Point 2), during 2009 and 2010 with three-hourly averages. The numerical model SWAN proved itself quite ...